Italian Studies on Quality of Life - Bianco, Adele; Conigliaro, Paola; Gnaldi, Michela (Social Indicators Research Series,, 2019)
This volume provides an overview of the ways the Italian school of quality of life studies addresses well-being and quality of life, from both a substantive and a methodological point of view. It discusses various topics such as those of equitable and sustainable wellbeing, lifestyles, the organization of economy and welfare, as well as aspects related to the measurement of quality of life in small towns, institutional transparency and corruption prevention indicators. Chapters presented in this volume are drawn from papers presented at the conferences of the Italian Association for Quality of Life Studies (AIQUAV) held in Florence, Italy, in 2015 and 2016. The volume is organised into three parts. The first part is devoted to methods and indicators for research on quality of life, the second part to social sustainability, lifestyles, cultural aspects and local applications, and the third to economy, welfare and quality of life. The volume hosts contributions that are interdisciplinaryin scope and mirror the complexity of the globalized world. .